ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN GREEN PRODUCT (STUDI KASUS PADA PRODUK LOVE BEAUTY AND PLANET DI KOTA MEDAN) - Prameswari, Ardhia; Atika, Atika; Harahap, Muhammad Ikhsan (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to identify aspects that can influence the decision to purchase green products in the city of Medan with a case study on LoveBeauty &Planet products. The method in this study is quantitative descriptive using primary data, with a sample of 100 valid respondents obtained through the distribution of questionnaires and processed using the Structural Equation Modeling Partial Least Square (SEM-PLS) analysis tool. By testing three independent variables, namely GPK (Green Product Knowledge), GPQ (Green Perceived Quality), and Life Style where these three variables will be tested for their effect on dependent variables, namely Buy Dec (Buying Decision). The results showed that the green product knowledge factor has a very small influence on consumer decisions, while the Green Perceived Quality factor influences consumer purchasing decisions and also Life Style has a significant influence on purchasing decisions.